2021
DOI: 10.1186/s12935-020-01707-9
|View full text |Cite
|
Sign up to set email alerts
|

PPP2R2B downregulation is associated with immune evasion and predicts poor clinical outcomes in triple-negative breast cancer

Abstract: Background Although immune checkpoint blockade has emerged as a novel promising strategy for triple-negative breast cancer (TNBC), many patients fail response or acquire resistance to current agents. Consequently, our focus need to shift toward alternative inhibitory targets, predictor for responsiveness, and immune suppressive mechanisms. Methods In this study, we performed systematic bioinformatics analyses to identify PPP2R2B as a robust tumor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…Weighted Gene Correlation Network Analysis procedure was carried out as described previously. 26 Briefly, a soft thresholding power of six was selected to generate a scale‐free topology from adjacency matrix. DeepSplit of 2 and minModuleSize of 30 were set as the parameters of the Dynamic Tree Cut method to avoid generating too many modules.…”
Section: Methodsmentioning
confidence: 99%
“…Weighted Gene Correlation Network Analysis procedure was carried out as described previously. 26 Briefly, a soft thresholding power of six was selected to generate a scale‐free topology from adjacency matrix. DeepSplit of 2 and minModuleSize of 30 were set as the parameters of the Dynamic Tree Cut method to avoid generating too many modules.…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that the antigen processing and presentation were weakened in the PPP2R2B low tumor cells. Thus, the measures to avoid PPP2R2B loss might be investigated to retain the more benign phenotype of cancer [ 170 ].…”
Section: Strategies To Overcome Immunotherapy Resistance Of Breast Cancermentioning
confidence: 99%
“…Downregulation of PPP2R2B reduces the effect of trastuzumab or lapatinib on mTOR signaling, thus weaken the anti-HER2 sensitivity 42 . What is more, PPP2R2B also involves in polarization of macrophages, the dysregulation of PPP2R2B would promote macrophages polarizing to M2, facilitating the immune evasion 43 . TSPAN7 inhibits the expression of E-cadherin and vimentin, which raises the level of N-cadherin44.…”
Section: Discussionmentioning
confidence: 99%